2012
DOI: 10.1038/jcbfm.2011.191
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Brain Oxygen Metabolism in Patients with Multiple Sclerosis with T2-Relaxation-Under-Spin-Tagging MRI

Abstract: In this study, venous oxygen saturation and oxygen metabolic changes in multiple sclerosis (MS) patients were assessed using a recently developed T2-relaxation-under-spin-tagging (TRUST) magnetic resonance imaging (MRI), which measures the superior sagittal venous sinus blood oxygenation (Yv) and cerebral metabolic rate of oxygen (CMRO 2 ), an index of global oxygen consumption. Thirty patients with relapsing-remitting MS and 30 age-matched healthy controls were studied using TRUST at 3 T MR. The mean expanded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
143
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(154 citation statements)
references
References 37 publications
7
143
4
Order By: Relevance
“…This reduction is consistent with 5.7% decrease of global OEF in patients with RRMS compared with controls, as measured by T2-relaxation-under-spin-tagging MRI in the sagittal sinus. 17 Figure 2. Magnitude and phase images (in radians) from gradientecho acquisitions in two patients with (A) relapsing-remitting MS and (B) secondary-progressive MS. For each patient, yellow arrows highlight one candidate vein, amenable to OEF analysis from phase, in the coronal and axial orientations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduction is consistent with 5.7% decrease of global OEF in patients with RRMS compared with controls, as measured by T2-relaxation-under-spin-tagging MRI in the sagittal sinus. 17 Figure 2. Magnitude and phase images (in radians) from gradientecho acquisitions in two patients with (A) relapsing-remitting MS and (B) secondary-progressive MS. For each patient, yellow arrows highlight one candidate vein, amenable to OEF analysis from phase, in the coronal and axial orientations.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal evaluations of OEF are needed in larger patient cohorts to better understand the relationship between metabolic changes and progressive disability in MS. Another limitation to this study is the lack of blood flow measurements, which can be coupled with OEF to directly quantify the cerebral metabolic rate of oxygen. Previous studies using phase-contrast and dynamic susceptibility contrast MRI have found either unchanged or reduced brain perfusion in MS, 17,46 indicating overall decrease in cerebral metabolic rate of oxygen. Thus, OEF changes describe a key component of hypometabolism in MS that is specific to neurons rather than glial cells, 47 and may offer an independent biomarker to understand the metabolic underpinnings of cognitive impairment in patients.…”
Section: Physiologic Interpretation Of Findingsmentioning
confidence: 99%
“…This leads to a reduced deoxygenation of the brain's venous blood and, consequently, less susceptibility-related signal loss on T2*w images [14,15]. This hypothesis is further supported by a quantitative MRI study that reported significantly increased venous oxygenation levels and decreased cerebral metabolic rates of oxygen in MS patients as compared with healthy controls [18]. Furthermore, vascular damage, a sequel of (perivascular) inflammation and gliosis [19] in MS, is associated with a globally reduced cerebral perfusion [20] and may thus contribute to diminished venous visibility on T2*w images [14,15].…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, vascular damage, a sequel of (perivascular) inflammation and gliosis [19] in MS, is associated with a globally reduced cerebral perfusion [20] and may thus contribute to diminished venous visibility on T2*w images [14,15]. Another possible cause of decreased oxygen uptake is the high level of nitric oxide (NO) due to repetitive vascular inflammation in MS competitively inhibiting mitochondrial uptake of oxygen in MS [18].…”
Section: Discussionmentioning
confidence: 99%
“…The study found a negative correlation between CMRO 2 and T 2 lesion volume, that is, the larger the lesion the lower the CMRO 2 , but that the CMRO 2 is independent of the total brain volume (Ge et al, 2012). The study found no significant change in global CBF, however.…”
mentioning
confidence: 91%